ASSESSMENT OF THE NUTRITIONAL BEHAVIOUR AMONG COLLEGE STUDENTS-A SURVEY - Begum, S. K. Shafiya; Kavuri, Naga Swathi Sree; Uppalapati, Mohan Chand; Polavarapu, Divya (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: To assess the nutritional behaviour among college students. Methods: A prospective observational survey was conducted randomly among college students in Guntur. A self-administered data collection form was designed to understand the nutritional behaviour of the subjects. Results: A total of 300 subjects were included in the study, among them 225(75%) were females and 75(25%) were males. The survey revealed that most of them skipped their meals. A majority of 184(61.33%) students opted for high-fat diet and 268(89.33%) opted for starch-rich foods. A total of 222(74%) students usually eat four different varieties of vegetables but only 71(23.66%) of them eat fruits in each week. Conclusion: From this study, it was evident that majority of students have poor dietary habits. Lack of awareness on balanced diet and due to their busy schedules, teenagers were not maintaining a proper diet. This could be reduced by bringing minimum awareness on dietary habits to them. Taking proper diet is very essential to reduce the risk of diseases in future and to improve nourishment.